The problem of organ transplantation based on three-sided stable matching - Ruya Fan; Yan Chen; Bo Shan (PLoS ONE, 2026)
Aiming at the problem of matching scarce resources among donors, recipients, and medical institutions in organ transplantation, a stable three-sided matching method is proposed. Firstly, in view of the preference structure characteristics of the problems in the context of organ transplantation, a mixed preference structure from the three-sided matching problem is introduced for description, and the stability conditions under this structure are also provided, intuitionistic fuzzy information was utilized to quantify uncertain indicators during organ transplantation. The Erlang distribution was introduced to describe the randomness of the occurrence of organ donors. Coping strategies for possible false reporting behaviors of organ recipients were designed, and a three-sided matching model of donors, recipients, and medical institutions was constructed. And proved the stability of this matching; Secondly, based on the NSGA-III algorithm, the initial search strategy of the Bird Swarm algorithm was introduced, a new mutation method was designed, and its feasibility was theoretically analyzed. Finally, the feasibility of the model and algorithm was verified through simulation examples in the context of organ transplantation, and the performance of the algorithm was analyzed and verified in combination with algorithm complexity, effectiveness, and ablation experiments. The experimental results show that the model and algorithm can effectively improve the stability of the matching results and increase the efficiency of resource allocation.